MtNODULE ROOT1 and MtNODULE ROOT2 Are Essential for Indeterminate Nodule Identity. Issue 1 (19th July 2018) - Magne, Kevin; Couzigou, Jean-Malo; Schiessl, Katharina; Liu, Shengbin; George, Jeoffrey; Zhukov, Vladimir; Sahl, Lucien; Boyer, Frederic; Iantcheva, Anelia; Mysore, Kirankumar S.; Wen, Jiangqi; Citerne, Sylvie; et al.
Abstract : The loss of function of MtNOOT1 and MtNOOT2 leads to the complete loss of nodule identity, prevents the symbiotic process, and results in the absence of nitrogen fixation in Medicago truncatula. Abstract: Symbiotic interactions between legume plants and rhizobia result in the formation of nitrogen-fixing nodules, but the molecular actors and the mechanisms allowing for the maintenance of nodule identity are poorly understood. Medicago truncatula NODULE ROOT1 ( MtNOOT1 ), Pisum sativum COCHLEATA1 ( PsCOCH1 ), and Lotus japonicus NOOT-BOP-COCH-LIKE1 ( LjNBCL1 ) are orthologs of Arabidopsis ( Arabidopsis thaliana ) AtBLADE-ON-PETIOLE1/2 and are members of the NBCL gene family, which has conserved roles in plant development and is essential for indeterminate and determinate nodule identity in legumes. The loss of function of MtNOOT1, PsCOCH1, and LjNBCL1 triggers a partial loss of nodule identity characterized by the development of ectopic roots arising from nodule vascular meristems. Here, we report the identification and characterization of a second gene involved in regulating indeterminate nodule identity in M. truncatula, MtNOOT2 . MtNOOT2 is the paralog of MtNOOT1 and belongs to a second legume-specific NBCL subclade, the NBCL2 clade. MtNOOT2 expression was induced during early nodule formation, and it was expressed primarily in the nodule central meristem. Mtnoot2 mutants did not present any particular symbiotic phenotype; however, the loss of function of both MtNOOT1 and MtNOOT2 resulted in the complete loss of nodule identity and was accompanied by drastic changes in the expression of symbiotic, defense, and root apical meristem marker genes. Mtnoot1 noot2 double mutants developed only nonfixing root-like structures that were no longer able to host symbiotic rhizobia. This study provides original insights into the molecular basis underlying nodule identity in legumes forming indeterminate nodules.